Determinan Kebahagiaan Individu Muslim di Indonesia - Dian Friantoro (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
Islam teaches its disciples to pray for happiness in the world and the hereafter. Indonesia, as the largest Muslim population in the world, can be a sample of how the context of Muslim happiness applied. This study aims to determine factors that affect Muslim’s individual happiness in Indonesia. The data was obtained from wave 5 of the Indonesian Family Life Survey (IFLS). It was then analyzed using the Ordinary Least Squares model. This study proves that all variables including religiosity, health, education, marital status, and income have a positive and significant effect on Muslim’s happiness level. The intensity of shalat (prayer) and religious affiliations have a positive and significant effect but the result is not necessarily robust. The frequency of attending taklim/ pengajian (mass religious gathering) does not influence the happiness level. This finding confirms that if all basic maslahah have been met, then a Muslim will be closer to achieving the presumed happiness.